Determinants of personal protective equipment utilization among healthcare workers - Ismarina; Dini Rachmaniah; Rita Ramayulis (KHD-Production, 2026)
Despite established guidelines, non-compliance with personal protective equipment (PPE) protocols remains a persistent challenge in healthcare settings, posing risks to occupational safety and infection prevention. This study examined factors associated with PPE use behavior among healthcare workers in inpatient units. An analytical cross-sectional study was conducted involving 260 healthcare workers. Data were collected via structured questionnaires and observational checklists. Associations between independent variables and PPE use behavior were assessed using chi-square tests. Inappropriate PPE use was observed in 60.8% of respondents. Bivariate analysis identified supervisory support (p = 0.011; OR = 2.315) and peer support (p < 0.001; OR = 4.470) as significant predictors of compliance. Conversely, age, education, knowledge, length of service, attitudes, comfort, and facility availability showed no significant association. Workplace social support, particularly from supervisors and colleagues, is a critical determinant of PPE compliance. Strategies to improve PPE adherence should prioritize strengthening organizational support systems rather than focusing solely on individual knowledge or resource availability.